O02-5 Workplace discrimination and mental health among ethnic minority workers in australia. (1st September 2016) - Reid, Alison; Chih, Jun; Carey, Renee; Darcey, Ellie; Gray, Corie
Abstract : Introduction: Discrimination occurs when a person is treated less favourably than another person in a similar situation because of their race, sex, ethnicity age or migrant status. It occurs at the organisational or individual level and can lead to work segregation where people are relegated to physically or psychologically burdensome jobs or to rude and dismissive behaviour. The aim of this project was to examine the prevalence of workplace discrimination among ethnic minority workers in Australia, and its impact on mental health. Methods: Current workers of Arabic, Chinese or Vietnamese background aged 18+ years were interviewed by telephone in English, Mandarin, Cantonese, Vietnamese or Arabic. The General Ethnic Discrimination Scale assessed recent and lifetime history of workplace discrimination and its stressfulness. The 5-item Mental Health Inventory assessed current mental health status. Univariate statistics and linear regression examined the association between demographic and occupational characteristics. Results: 585 workers (51% female; 195 from each group) participated in the survey. 18% of Arabic, 77% of Vietnamese and 52% of Chinese interviewed in a language other than English. Occupation varied by ethnic group with 42% of Vietnamese in labouring, machine operating or sales jobs compared with 26% Arabic and 24% Chinese. The prevalence of recent (31% p = 0.17) and lifetime (55% p = 0.14) discrimination did not vary between groups. However, after adjusting for age, sex, language of interview, occupation, and year of arrival in Australia, Arabic workers reported a twofold increase in discrimination-related stress (Coef 2.34, 95% CI: 1.25–3.42) and significantly poorer mental health scores (Coef −2.3–95%CI: −4.3 −0.3) compared with Chinese workers, which further reduced after adjusting for discrimination-related stress (Coef −4.2, 95% CI: −7.3–1.2). Discussion: While prevalence of work-related discrimination was similarly high among all workers, the stressfulness of that discrimination varied between groups. Discrimination-related stress was associated with poorer mental health among Arabic workers.